Ethnic minority students' beliefs about English language learning-A survey at Sam Son pre-university school - Tran, Thi Phuong Hoa (ĐHNN, 2017)
Language learners hold a set of beliefs concerning language learning and these beliefs may influence the ways they learn, even though the beliefs are not always explicitly stated. This study deals with the results of a research project conducted among 150 (...)